Teaching with soap: Examples of project-based units for students and future educators. (2nd April 2016) - Farrell, Ivan; Hamed, Kastro M.
ABSTRACT: This article describes the use of project-based instruction in activities and labs intended to develop higher-order thinking skills with high school students and pre-service teachers through the use of soap making.